Mann and Ishikawa iteration schemes for multivalued mappings in CAT(0) spaces - Puttasontiphot T. (2017)
In this paper, we prove strong convergence theorems for the Mann and Ishikawa iteration schemes involving quasi-nonexpansive multivalued mappings in the framework of CAT(0) spaces. The results we obtain are analogs of Banach space results of Shahzad and Zegeye [13].